Comparative Analysis of Armenian and English Syndetic Analytical Word-Formation Structures with Noun Component - Karapetyan, Sirarpi (Armenian Folia Anglistika, 2017)
The syndetic or conjunctional analytical word-formation structures with noun component are very productive in the Armenian and English languages from the point of view of forming new words. The paper is devoted to the comparison and contrast of the structural, grammatical and semantic peculiarities of the syndetic (conjunctional) analytical word-formation structures in Armenian and English. In Armenian they are mainly formed with the help of the conjunction “ու”, rarely with the conjunction “և”. In English these units are generally formed with the help of the conjunction “and” and belong to the type of the so-called phrase compounds. Besides the conjunctional compounds, phrasal compounds also include the so called syntactic compounds which resemble segments of speech corresponding to the syntactic and word order rules of the English language, e.g. Jack-of-all-trades “a person who can do many different kinds of work”, lily-of the-valley “a European plant of the lily family”; this type does not have its typological equivalent in Armenian. The examples of syndetic analytical structures provided in this paper are mainly taken from English and Armenian dictionaries.
Keywords: analytical structures; compound; phrase; word-formation; comparative analysis; typology; noun; component